Sources of future growth in Indian irrigated agriculture - Svendsen, Mark (International Food Policy Research Institute, 1990)
Modern Indian irrigation development goes back in time at least to the construction of the Western Yamuna Canal near Delhi in 1355 by Ferozshah Tughlaq. Much earlier irrigation development in the subcontinent was undertaken by the Harappa and Mohen-jo-daro civilizations of 2500 B.C. and the builders of irrigation tanks in South India and Sri Lanka (Rogers 1983). By 1900, British India^ had about 13.2 million ha of total irrigated area, including 7.5 million ha of public works (4.5 million ha from large-scale public works and 3.0 million ha from minor public works) and 5.7 million ha of private works (4.0 million ha from private wells and 1.7 million ha from other private works) (India, Ministry of Irrigation and Power 1972).